Trans-oral partial epiglottidectomy to treat dysphagia in post-treatment head and neck cancer patients: a preliminary report - Jamal, Nausheen (2013)
OBJECTIVES: To determine symptoms and findings in patients with dysphagia related to epiglottic dysfunction. To analyze outcomes in patients who underwent partial epiglottidectomy due to dysphagia related to epiglottic dysfunction STUDY DESIGN: Review and analysis of clinical data obtained as part of the diagnosis and treatment of patients with dysphagia related to epiglottic dysfunction. METHODS: A retrospective review was performed of all post-treatment head and neck cancer patients who underwent epiglottidectomy at a single tertiary care referral center. Objective pre- and post-procedure swallow findings, endoscopic evaluation, and subjective improvement based on patient self-report were reviewed. RESULTS: Seven patients were identified based on endoscopic evaluation and modified barium swallow study (MBSS) as having epiglottic pathology leading to dysphagia. Specific anatomic and functional findings included thickening of the epiglottis, absence of epiglottic deflection, vallecular bolus retention during and after the swallow, and bolus backflow from the pharynx to the oral or nasal cavity. Partial epiglottidectomy was performed in these patients. Post-operative MBSS was analyzed for changes in swallow efficiency and safety. Nearly all patients demonstrated improved pharyngeal bolus passage with little to no added swallowing morbidity. CONCLUSIONS: Preliminary findings suggest a role for partial epiglottidectomy in post-treatment head and neck cancer patients with swallowing disorders. Ideal candidates have intact tongue base contraction and poor retroflexion of the epiglottis, which result in bolus obstruction at the level of the valleculae. Partial epiglottic resection enables improved bolus passage in the pharyngeal phase. Minimal post-operative morbidity occurs in the appropriately selected patient.